Beyond either/or: Reading trans* lesbian identities. - Gailey, Nerissa; Brown, A D (Journal of Lesbian Studies, 2016)
Previous research has explored the affiliation and distancing strategies employed in published memoirs of gender transition. In this article, we are particularly interested in elucidating the ways in which individuals construct identities and characterize their sexualities, and how sociohistorical constraints might influence what is expressed with respect to this in personal narratives of transition. Using the memoirs of Lili Elbe (Hoyer, 1933) and Joy Ladin (2013) as conceptual brackets, this article investigates the complex relationship between the development and articulation of trans* identities and lesbian sexualities within the context of published memoirs of gender transition.
3 citations (Crossref) [2023-10-31] Place: England Gailey, Nerissa. a Carleton University, Ottawa, Ontario, Canada. Brown, A D. b Southern Connecticut State University, New Haven, Connecticut, USA.
Keywords: *Homosexuality; Female/px [Psychology]; *Transgender Persons/px [Psychology]; Female; Gender Identity; Homosexuality; Female; Humans; Lesbian; Male; Personal Narratives as Topic; Sex Reassignment Surgery; Sex Reassignment Surgery/px [Psychology]; Transgender Persons; Women's Rights; dept.soc; female; feminist movements; gender identity; human; identity; lesbianism; literature; male; memoirs; psychology; sex reassignment; sexuality; trans*; transgender; women's rights